Literature review on Amukkira Chooranam in Siddha Medicine - Prasad, V.M.; Kopinisha, V. (University of Jaffna, 2020)
Siddha Medicine is one of the ancient medical systems which have its foundations laid by Siddhars. It is well known for its significant beneficial effects and lesser known side effects. Amukkira is one of the commonly used herbs in Siddha. Although many review articles on this plant were already published, this study reviews the commonly used drug “Amukkira chooranam” using Amukkira as one of the ingredient. The review was done on ingredients, organoleptic characters, dosage, anupana, diseases, and actions of ingredients. Authors have reviewed 14 text books to collect the data. In 14 books 19 different methods for Amukkirachooranam were identified using 56 different ingredients. These books have mentioned 7 to 35 ingredients. Rock salt and Red sulphide of mercury are stated as ingredients for Amukkirachooranam which have to be detoxified before being used in medicines. Out of 56, 25: 67.38% of ingredients have taste as pungent and 20: 29.68% bitter, 35: 76.08% as hot in potency and 35: 77.78% as pungent vipaham. Three books mentioned the dosage as verugadipiramanam 2 times a day for one mandalam. Hot water, honey, ghee and sugar are mentioned as anupanam and it is commonly used for the treatment of anaemia, vaayvu, kapha disease, gunmam rickets and poisoning (rat and insect bite poisoining, Viriyan snake, Sil, Scorpion bite poisoning). Carminative (16.52%), stimulant (15.70%), stomachic (14.87%), tonic (11.57%) are the common main actions. Therefore “AmukkiraChooranam” is one of the most useful siddha drug and further lab study and clinical trial should also be conducted.
Keywords: Amukkira chooranam; Siddha Medicine; Literature review